USER-GENERATED REVIEWS AND OFFICIAL STAR RATINGS: CAN THE TWO WORK TOGETHER IN HOTEL EVALUATION SYSTEMS? - Femi Odebiyi; Vitaliya Gontar (Economic Review)
The purpose of this study is to understand the emerging influence of e-WOM (electronic word-of-mouth) as a contemporary feedback system, its role for hotels, and importance for guests. Furthermore, the study identifies the nature of user-generated feedback in terms of determining hotel ratings, and establishing whether similarities between official hotel ratings and guests’ feedback evaluations exist. The qualitative study is based on the analysis of 240 feedbacks, taken from the TripAdvisor.com, for 20 hotels of 3 and 4 star ratings in Klaipeda (Lithuania) and Kaliningrad (Russia), and interviews of eight hoteliers. The most important review categories for guests were found to be that of amenities, service, and location. The findings reveal that the online review system is still not structured enough to become the main evaluation system of a hotel.